Tangshen Formula Improves Diabetes-Associated Myocardial Fibrosis by Inhibiting TGF-β/Smads and Wnt/β-Catenin Pathways - Hu, Lin; Wang, Yuyang; Wan, Yuzhou; Ma, Liang; Zhao, Tingting; Li, Ping (Frontiers in Medicine, 2021)
Cardiovascular disease has become the main cause of death among complications of diabetes. Myocardial fibrosis is a crucial pathological change of cardiovascular disease. Tangshen Formula (TSF) shows well clinical effect in the treatment of diabetic kidney disease. However, whether TSF alleviates diabetes-associated myocardial fibrosis still unknown. In the present research, we studied the effect and mechanism of TSF in the treatment of myocardial fibrosis in vivo and in vitro. Here, we found TSF treatment significant downregulate myocardial fibrosis including collagens I and III, α-SMA. Meanwhile, TSF improved fibrotic damage of TGFβ1-induced primary mouse cardiac fibroblast. Moreover, TSF decreased the expression level of TGF-β/Smad-related gene (α-SMA, collagens I and III, TGF-β1, pSmad2/3), while increased Smad7 gene expression. In addition, TSF decreased the expression of wnt1, active-β-catenin and MMP7 to regulate Wnt/β-catenin pathway. Taken together, TSF appears to ameliorate myocardial fibrosis in KKAy mice by inhibiting TGF-β/Smad2/3 and Wnt/β-catenin signaling pathways.